Estudo do tópico discursivo como estratégia argumentativa no projeto polêmicas em debate - Pereira, Ana Rafaella Alves (Universidade Federal Rural do Semi-Árido, 2019)
The study of the discursive topic allows the knowledge that the identification of the topic of a text is essential for its comprehension. At the moment of interaction, the interlocutors can keep, change or resume the topic. Thus, this research is centered on the teaching of the discursive topic as an argumentative strategy in the “Polêmicas em debate” project. This project has been promoting Portuguese language teaching for seven years and aims to debate controversial themes that circulate in society. Thus, it uses the controversial background debate to enable the arguments and the defense of the participants' point of view. Therefore, it is believed that it is possible to teach the topic as an argumentative strategy based on the debate in Portuguese high school classes. The aim of this study is to research how the argumentative strategies take place in the controversial background debate held in the “Polêmicas em Debate” project, considering the deviation and maintenance of the discursive topic. Therefore, studies of the discursive topic were related to those of the debate and the theories of argumentation. In order to achieve this objective, the discussions were supported by Jubran (1993), Pinheiro (2012) and Cavalcante (2012) to study the discursive topic; Bakhtin (1997), Marcuschi (2007), Dolz, Schneuwly and Pietro (2004) to address orality; Perelman e Tyteca (2017), Koch and Elias (2016) to treat about argumentation. The teaching of the debate genre enables the systematization of orality that can be anchored in several strategies, from which the discursive topic was chosen as an argumentative strategy. From the specific objectives the study seeks to identify how the deviation from the discursive topic can be configured as an argumentative strategy for face protection of the debate participants; and analyze how maintaining the discursive topic can be a means of strengthening the arguments presented by the debaters. The research is qualitative and also a case study based on Prodanov (2013), Yin (2001) and Gil (2008). As a methodological path to achieve the objectives, we analyzed the transcripts of two videos of the debates that were recorded during the “Polêmicas em debate” project under discussion in 2017 from the procedures listed in the methodology. The results of the analysis showed that, in defending their thesis, some debaters used maintenance when they made use of topics that were directly related to the central topic of the debate. Deviation was found to be a face protection strategy when the debater made use of topics that were not directly related to the central topic. In addition, the degree of complexity of the arguments was analyzed by dividing them into three levels: low, medium and high. Thus, it was concluded that it is possible to teach the discursive topic through the oral genre debate that allows the development of oral language and logical reasoning, as well as the argumentative strategies in Portuguese language classes
Keywords: Tópico discursivo; Gênero oral; Debate; Ensino; Argumentação; Discursive topic; Orality; Debate; Teaching; Argumentation; MULTIDISCIPLINAR::ENSINO